Finding an Efficient Network Medium: Wi-Fi or Li-Fi - Shruti; Sharma, Osheen (International Journal of Computer Sciences and Engineering, 2025)
In today’s world where wireless technology is dominating the world, new methods are being invented each day to make wireless communication fast and efficient. One of the most popular one is Wi-Fi. It is available in almost every office, college, airport, railway station, restaurants, etc. It provides easy and quick access to internet whenever we are in need. But along with its easy availability and advantages, there are some disadvantages also. Wi-Fi requires a proper infrastructural setup and consumes more power. Moreover, it makes use of radio waves for data transmission that is harmful to our health. So, to make wireless communication more efficient and overcome disadvantages of Wi-Fi, researchers have introduced new technology called Li-Fi. It uses Light Emitting Diodes as a light source to transmit data, which makes it cheaper and more operative compared to Wi-Fi. Though Li-Fi is not being used commercial yet but in near future it is surely going to hit the wireless communication industry. In this paper, we are going to study about both Wi-Fi and Li-Fi along with which a detailed comparison between both of these technologies has been done.